Peranan pemasaran media sosial selama pandemi Covid-19 - Nyoko, Antonio Eli Lomi (Jurnal Manajemen Maranatha, 2022)
This study aims to determine the role of social media marketing during the COVID-19 pandemic in the culinary industry in Kupang City by observing social media marketing behavior on Facebook Group Bekin Lapar. The method that is used in this study is to observe on Facebook Group: Group Bekin Lapar then conducted data triangulation from observation, documentation, and interview and made the conclusions about the role of social media marketing during the COVID-19 pandemic in the culinary industry in Kupang City. The study concluded that the role of social media marketing in Facebook Group: Group Bekin Lapar is significant to promote, sell, recommend the products of group members, and find information about culinary products in Kupang City during the COVID-19 pandemic. Recommendation to other culinary businesses in other cities is to optimize the role of social media marketing to promote and sell their product during the COVID-19 pandemic.